STUDIES ON THE RECOVERY OF COLD-SHOCKED Staphylococcus aureus ISOLATED FROM PROCESSED MARTEDELLA AND PASTRAMI USINF SODIUM PYRUVATE AS GROWTH-PROMOTER - Abdullah, Samia Abdurrahman; Elfaki, Ahmed Elawad; ElSanousi, S. M. (Journal of Veterinary Medicine and Animal Production, 2021)
The main objective of this research was to study the recovery of cold- shocked injured Staphylococcus aureus isolated from contaminated processed meat. Sodium pyruvate was used as a supplement and added to Baird Parker’s medium for the recovery of the injured Staphylococcus aureus by cold shock. Thirty samples of Martedella and Pastrami were collected from different manufactures and supermarkets at Khartoum state (Omdurman, Bahry). A full loop of Staphylococcus aureus was added to a test tube containing peptone water. The suspension was incubated at 37°C for 24hrs. From the serial dilutions 0.1ml was inoculated on Baird Parker’s medium prepared with different concentrations of sodium pyruvate(0.5%, 1.0%and1.5%) and incubated at 37 °C for 48 hrs. The same procedure was followed for shocked bacteria at -20°C,-30 °C and -40 °C. The results of the sodium pyruvate concentrations treatments showed that at -20 °C the recovery of the injured bacteria was 82.35%, 85.71%and 75.82%, respectively. While at -30 °C the recovery of the injured bacteria was 86.96%, 68.18%and 0.40%, respectively. Whereas at -40°C the recovery was 24.69%, 43.48%and 47.62%, respectively. It is concluded that the addition of sodium pyruvate in concentrations (0.5%, 1% and1.5%) to recover shocked bacteria at temperature-20°C and the concentration (0.5%) at temperature-30°C had a beneficial recovery of injured cells of Staphylococcus aureus . The recovery rates decrease directly proportional with the temperature decrease.